Reorganization of 3D chromatin architecture in doxorubicin-resistant breast cancer cells - Wang, Xuelong; Yan, Jizhou; Ye, Zhao; Zhang, Zhiqiang; Wang, Sheng; Hao, Shuang; Shen, Baiyong; Wei, Gang (Frontiers in Cell and Developmental Biology, 2022)
Background: Doxorubicin resistance remains a major therapeutic challenge leading to poor survival prognosis and treatment failure in breast cancer. Although doxorubicin induces massive changes in the transcriptional landscape are well known, potential diagnostic or therapeutic targets associated with the reorganization of three-dimensional (3D) chromatin architecture have not yet been systematically investigated. Methods: Here we performed in situ high-throughput chromosome conformation capture (Hi-C) on parental and doxorubicin-resistant MCF7 (MCF7-DR) human breast cancer cells, followed by integrative analysis of HiC, ATAC-seq, RNA-seq and TCGA data. Results: It revealed that A/B compartment switching was positively correlated to genome-wide differential gene expression. The genome of MCF7-DR cells was spatially reorganized into smaller topologically associating domains (TADs) and chromatin loops. We also revealed the contribution of increased chromatin accessibility and potential transcription factor families, including CTCF, AP-1 and bHLH, to gained TADs or loops. Intriguingly, we observed two condensed genomic regions (~20kb) with decreased chromatin accessibility flanking TAD boundaries, which might play a critical role in the formation or maintenance of TADs. Finally, combining data from TCGA, we identified a number of gained and lost enhancer-promoter interactions and their corresponding differentially expressed genes involved in chromatin organization and breast cancer signaling pathways, including FA2H, FOXA1 and JRKL, which might serve as potential treatment targets for breast cancer. Conclusion: These data uncovered a close connection between 3D genome reorganization, chromatin accessibility as well as gene transcription and provide novel insights into the epigenomic mechanisms involving doxorubicin resistance in breast cancer.